A STUDY OF NUTRITIONAL STATUS AND FOOD CONSUMPTION BEHAVIOR OF HOME ECONOMICS STUDENTS FACULTY OF SCIENCE AND TECHNOLOGY PIBULSONGKRAMRAJABHAT UNIVERSITY - Singsom, Susitra (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2020)
The objective of this research was to study the nutritional status and food consumption behavior of home economics students. Faculty of Science and Technology Pibulsongkram Rajabhat University Phitsanulok Province The population studied is students of home economics program. Faculty of Science and Technology, Year 1-4, a total of 239 people were collected by using questionnaires. Data were analyzed by using percentage, mean, standard deviation. Pearson Correlation statistics were analyzed. The results showed that 1) students were 75.3 percent female, 24.7 percent male, 2) 29.3 percent were 20 years old, 23.0 percent were aged 3) 3) 99.6 percent were Buddhists, Christianity 0.4% 4) Year 3 level 27.6% Year 4 level 26.8% 5) The most common symptoms are 12.1 percent are easily tired, dizzy, dizzy, 11.7 percent, dizziness 6) have nutritional status according to BMI with normal weight 40.6 percent (= 23.66, SD = 5.648), followed by extreme obesity / obesity level 3 16.3% underweight / thin 14.6% 7) Most of the students’ food consumption behavior is at a fair level 94.6% ( = 49.08, SD = 5.093), followed by a good level of 4.6%. Improve by 0.8 percent, found that the most frequent dietary habits are See the expiration date before buying ready-made food 47.7%